MRI‐guided high‐intensity focused ultrasound ablation of bone: Evaluation of acute findings with MR and CT imaging in a swine model. Issue 5 (7th November 2013) - Bucknor, Matthew D.; Rieke, Viola; Do, Loi; Majumdar, Sharmila; Link, Thomas M.; Saeed, Maythem
<x xml:space="preserve">Abstract</x> Purpose To evaluate hyperacute (<1 hour) changes on magnetic resonance (MR) and computed tomography (CT) imaging following MR‐guided high‐intensity focused ultrasound (MRgHIFU) in a swine bone model as a function of sonication number and energy. Materials and Methods Experimental procedures received approval from the local Institutional Animal Care and Use Committee. MRgHIFU was used to create distal and proximal ablations in the right femur of eight pigs. Each target was dosed with four or six sonications within similar volumes. The energy dosed to the distal target was higher (419 ± 19 J) than the proximal target (324 ± 17 J). The targeted femur and contralateral control were imaged before and after ablation using MR at 3T. Qualitative changes in signal on T1‐weighted, T2‐weighted, and T1‐weighted postcontrast images were assessed. Ablation dimensions were calculated from postcontrast MRI. The 64‐slice CT images were also obtained before and after ablation and qualitative changes were assessed. Results MRgHIFU bone ablation size measured on average 8.5 × 21.1 × 16.2 mm (transverse × craniocaudal × anteroposterior). Interestingly, within similar prescribed volumes, increasing the number of sonications from 4 to 6 increased the depth of the intramedullary hypoenhanced zone from 2.9 mm to 6.5 mm (P < 0.001). There was no difference in the appearance of low versus high energy ablations. CT imaging did not show structural abnormalities. Conclusion The number of MRgHIFU focal sonications can be used to increase the depth of treatment within the targeted bone. Unlike CT, T2‐weighted and contrast‐enhanced MR demonstrated the hyperacute structural changes in the femur and surrounding soft tissue.J. Magn. Reson. Imaging 2014;40:1174–1180 © 2013 Wiley Periodicals, Inc.